A methodology for mapping native and invasive vegetation coverage in archipelagos: An example from the Galápagos Islands. (February 2018) - Rivas-Torres, Gonzalo F; Benítez, Fátima L; Rueda, Danny; Sevilla, Christian; Mena, Carlos F
This study develops a mixed, systematic, low-cost methodology to define and map native vegetation and the spread of the most aggressive invasive species in islands biomes, focusing on the Galápagos National Park (GNP). Based on preliminary legends defined by experts, Landsat 8/OLI fusion imagery was used for object-oriented classification to obtain the vegetation map of this archipelago. This technique was later verified and validated using high-resolution images from unmanned aerial vehicles (UAVs, i.e., drones) and dedicated satellites, ground truthing, and visual confirmation around GNP coasts. This mixed methodology allowed mapping of nine native ecosystems, six invasive-dominated vegetation units, and two types of lavas. Around 53.63% of GNP is covered by native ecosystems and ∼2.2% is "canopy" dominated by invasive species to date. Native-dominated deciduous forest types cover ∼40.8% of the GNP and only ∼12.8% of the protected area is nowadays covered by humid and transitional type native ecosystems. Among humid native ecosystems, those distributed in the highlands only cover 4.8% and are highly threatened by invasive species, which are mostly distributed in these summit areas. Of the five islands (out of 18) recording invasive-dominated units, Isabela and Santa Cruz were the most infested. Cedrela odorata, Pennisetum purpureum, and Psidium guajava were the main invasive plants dominating the GNP canopy. Highly noxious Rubus niveus was the only invasive species dominating areas among the five infested islands. Methodology detailed here proved useful to provide accurate spatially-explicit islands vegetation data, potential for replication in time, and is expected to aid suitable management of highly endangered and unique biotas in this and other tropical island biomes.